2017
DOI: 10.1155/2017/4716197
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aerobic Exercise on Brain-Derived Neurotrophic Factor in People with Neurological Disorders: A Systematic Review and Meta-Analysis

Abstract: Objective To determine the effect of aerobic exercise on brain-derived neurotrophic factor (BDNF) levels in people with neurological disorders. Data Sources Six electronic databases (CINAHL, PubMed, Cochrane, PsycINFO, SportDiscus, and Web of Science) were searched until the end of December 2016. Study Selection Experimental or observational studies of people with neurological disorders who undertook an exercise intervention with BDNF as an outcome measure. The search strategy yielded 984 articles. Data Extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 48 publications
4
58
0
5
Order By: Relevance
“…In the present study, aerobic exercise has been shown to enhance BDNF expression (Marais et al, 2009;Marlat et al 2012). This finding is in accordance with previous study in which treadmill training increased BDNF protein levels in the striatum (Szuhany et al, 2016;Mackay et al, 2017). BDNF promotes survival and proper function of neuronal population.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, aerobic exercise has been shown to enhance BDNF expression (Marais et al, 2009;Marlat et al 2012). This finding is in accordance with previous study in which treadmill training increased BDNF protein levels in the striatum (Szuhany et al, 2016;Mackay et al, 2017). BDNF promotes survival and proper function of neuronal population.…”
Section: Discussionsupporting
confidence: 93%
“…), the fact that our stroke subjects did not reach comparable levels of high intensity exercise (lactate > 10 mmol/l) to healthy adults who participated in the previous priming studies may have also influenced the BDNF secretion (Mackay et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the potential limitations of measuring BDNF in humans (Charalambous et al 2018), findings on whether exercise-induced BDNF changes are correlated with gains in motor learning in neurologically intact adults are mixed (Mang et al 2014;Skriver et al 2014). Including the potential effects of age, gender and neurological condition on the peripheral measures of BDNF (Knaepen et al 2010;Szuhany et al 2015;Santos et al 2016), the fact that our stroke subjects did not reach comparable levels of high intensity exercise (lactate > 10 mmol/l) to healthy adults who participated in the previous priming studies may have also influenced the BDNF secretion (Mackay et al 2017).…”
Section: Effect Of Exercise On Learning May Be Context Specificmentioning
confidence: 92%
“…31,32 Moreover, previous studies performed in human and animal models have demonstrated the role of physical exercises as a stimulating factor of neural plasticity by the increase of brain-derived neurotrophic factor (BDNF) levels, axonal regeneration, and the promotion of long-term potentiation (LTP)-like plasticity in the motor cortex. [33][34][35][36] Also, physical exercise has been proven to provide beneficial effects in the cerebellar mitochondrial bioenergetics systems of rats, 37 and this could be used as a model for a therapeutic approach for SCA2 patients in which the bioenergetic deficits caused by the ataxin-2 mutation 38-40 could be alleviated.…”
Section: Discussionmentioning
confidence: 99%